2017
DOI: 10.1108/wwop-10-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Community-based research and approaches to loneliness prevention

Abstract: Purpose The purpose of this paper is to report on research with older people that explored experiences of loneliness in order to consider community level approaches to prevent and reduce feelings of loneliness. Design/methodology/approach This research was co-produced with a community research group and involved a series of in-depth interviews (n=14) with older people. Interviews were thematically analysed. Findings Analysis revealed three key themes: connecting and disconnecting, points of vulnerability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Additionally, it has been argued that loneliness is not only about how people view themselves, but also about how they feel they are positioned in society. Societal and community level responses to loneliness include both a normalization of loneliness and manufactured opportunities to re/engage with local communities in later life (Barke, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been argued that loneliness is not only about how people view themselves, but also about how they feel they are positioned in society. Societal and community level responses to loneliness include both a normalization of loneliness and manufactured opportunities to re/engage with local communities in later life (Barke, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they could ask family members to have a video call at a certain time each week or create online social activities for groups of residents. Community-based approaches and social connections can help improve technology adoption and reduce feelings of loneliness and social disconnectedness (Barke, 2017).…”
Section: Considerations For Implementationmentioning
confidence: 99%
“…This may take the form of public health campaigns and re-establishing access to events. Thirdly, we propose that collective events and community interventions (including face-to-face and digital) may be more effective than individual solutions, in order to reinstate access to feelings of community belonging as psychological resources (see Barke, 2017;Bowe et al, in press;McNamara et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative, lived experienced research has found that chronic loneliness in later life is associated with feelings of being trapped, fear of the future, grief for the past, a perceived powerlessness and inability to resolve feelings of loneliness, and shame and defeat (Barke, 2017;Hauge & Kirkevold, 2012;Roos & Klopper, 2010;Taube et al, 2016). Further, cognitive psychologists have found that people who are chronically lonely tend to experience increasing social anxiety and paranoia of others (Cacioppo & Hawkley, 2009;Canham, 2015), are hyper-vigilant for social threats (such as hostility from others), and experience increased depression and difficulty in generating satisfactory social connections (Cacioppo et al, 2006;Heinrich & Gullone, 2006;Segel-Karpas & Ayalon, 2020).…”
Section: Ageing and Loneliness Experiencesmentioning
confidence: 99%